2017
DOI: 10.3174/ajnr.a5436
|View full text |Cite
|
Sign up to set email alerts
|

Association between Carotid Plaque Features on CTA and Cerebrovascular Ischemia: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: CTA is a widely available imaging examination that may allow the evaluation of high-risk carotid plaque features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 36 publications
2
43
0
2
Order By: Relevance
“…Our results agree with previous findings (in carotid arteries), which suggested that larger plaques (defined by their width or height), were not associated with any particular composition or vulnerability characteristics [12,41]. Studies in coronary arteries showed no association between the lipid core size and plaque surface area [42].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our results agree with previous findings (in carotid arteries), which suggested that larger plaques (defined by their width or height), were not associated with any particular composition or vulnerability characteristics [12,41]. Studies in coronary arteries showed no association between the lipid core size and plaque surface area [42].…”
supporting
confidence: 91%
“…Then, plaques with high lipid content were associated with a predominant lipid content in the 1st mm. Related with this, plaques would be vulnerable because of the overall lipid content and also due to the absence of a fibrous cap, associated with the lipid content prevailing in the 1st mm, characteristics that increase risk of erosions and ruptures that favor plaque accident [12,28,41]. Taking into account the above, assessing the composition of the 1st mm may be sufficient in case of limitations to determine the composition of the whole plaque.…”
mentioning
confidence: 99%
“…Also, differences in window width and level and in administered contrast amount and density can produce interoperator variability about the reported lumen size. In the evaluation of significant carotid stenosis, CTA yields an overall sensitivity of 97 % and specificity of 99 % [25].…”
Section: Karotis-erkrankungmentioning
confidence: 99%
“…Although mcMRI can detect large IPHs, it misses about half of small or heavily calcified IPHs . Of potentially greater concern, mcMRI cannot differentiate hemosiderin‐rich hemorrhage associated with rupture risk from calcification that indicates plaque stability and reduces the risk of arterial embolization by half …”
Section: Introductionmentioning
confidence: 99%